2018
DOI: 10.3390/a11050070
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Functional Connectivity Symmetry between Oxy- and Deoxy-Haemoglobin: Implications for fNIRS Connectivity Analysis

Abstract: Functional Near InfraRed Spectroscopy (fNIRS) connectivity analysis is often performed using the measured oxy-haemoglobin (HbO 2 ) signal, while the deoxy-haemoglobin (HHb) is largely ignored. The in-common information of the connectivity networks of both HbO 2 and HHb is not regularly reported, or worse, assumed to be similar. Here we describe a methodology that allows the estimation of the symmetry between the functional connectivity (FC) networks of HbO 2 and HHb and propose a differential symmetry index (D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 65 publications
0
17
0
1
Order By: Relevance
“…However, most of previous fNIRS work only reported the neuroimaging results based on HbO signals. 58 In this study, both HbR and HbO data were analyzed to generate the brain activation and construct the brain networks.…”
Section: Functional Near-infrared Spectroscopy Data Acquisition and Pmentioning
confidence: 99%
“…However, most of previous fNIRS work only reported the neuroimaging results based on HbO signals. 58 In this study, both HbR and HbO data were analyzed to generate the brain activation and construct the brain networks.…”
Section: Functional Near-infrared Spectroscopy Data Acquisition and Pmentioning
confidence: 99%
“…We also found that DTW-ΔHb and CC-ΔHbO feature sets showed higher classification scores for classification of flourishing levels of individuals. In general, fNIRS based connectivity studies generally utilizes ΔHbO and ΔHbO signals have higher signal-to-noise ratio (SNR) than ΔHb signals (Homae et al, 2010; Montero-Hernandez et al, 2018a; Niu et al, 2011; Y. J. Zhang et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…After performing the preprocessing pipeline, to estimate functional connectivity matrices, we used both CC and Dynamic Time Warping (DTW) distance between all channels for all participants by utilizing ΔHb and ΔHbO time series. In contrast to conventional approach that uses ΔHbO for FC analysis, we also used ΔHb due to previous evidence that suggests both hemoglobin concentrations should be analyzed for sparse networks (Montero-Hernandez et al, 2018b). In addition to this, there are several fNIRS based ML studies that focuses on classification of several psychiatric disorders also uses ΔHb (Cheng et al, 2019; Crippa et al, 2017; Hernandez-Meza et al, 2018; Hernandez-Meza et al, 2017; J.…”
Section: Methodsmentioning
confidence: 99%
“…The Jaccard index is the ratio of the intersection over the union of two sets, and when applied to graphs it is computed over the sets of edges. 17 …”
Section: Methodsmentioning
confidence: 99%
“…The Jaccard index is the ratio of the intersection over the union of two sets, and when applied to graphs it is computed over the sets of edges. 17 Given the nonstatistical nature of IFM, we further suggest an alternative graph isolating algorithm that can be used in circumstances when no other standard is present, yet a graph is required as a solution. This alternative algorithm looks for a topologically stable region by examining the change in the number of connected components in the graph and choosing the one that lives longer.…”
Section: Validationmentioning
confidence: 99%